Student Activity in Suboptimal Thermal and Acoustic Conditions: An In-Field Study in Active Classrooms - Giulia Fratoni; Domenico De Salvio; Virginia Tardini; Massimo Garai; Paolo Valdiserri; Cesare Biserni; Dario D’Orazio (Applied Sciences)
This document provides a comprehensive overview of in-field measurements of acoustic and environmental conditions in three university lecture halls, focusing on their impact on student activity levels. The study, conducted at the University of Bologna, aims to measure student activity (SA) levels under unfavorable comfort conditions: high occupancy density, low teacher intelligibility, and absence of ventilation. The measurements show that, under these conditions, the student activity level is neither correlated with the room’s thermo-hygrometric conditions nor occupancy levels. The results, on the other hand, indicate that there is an inverse relationship between the SA level and occupancy: the higher the occupancy, the lower the SA level. Under conditions of high occupancy density and suboptimal thermal conditions, the mechanisms underlying student activity appear to differ from those observed in previous studies conducted under lower occupancy density. In the latter, an increase in SA levels was measured as occupancy increased. In contrast, the present study highlights an inverse behavior where students tend to reduce their activity as the number of students increases.